Does people oriented urbanization catch up with land and population urbanization - Tianci Gu; Qingxu Huang; Mingxing Chen; Chunyang He; Guoliang Zhu; Yiming Hou; Yihan Zhou; Kaihong Yue; Ming Zhang; Shiyu Zhang; Yizhou Xie; Jiasheng Wang (npj Urban Sustainability)
Abstract Recently, China has undergone rapid urbanization in terms of population and urban land growth. However, there are notable lags in the people-oriented dimensions of urbanization, including urban social services, environmental services, and socioeconomic equity, which are crucial for achieving SDG11 (sustainable cities and communities). Here, considering the complex dimensions of urbanization, we examined 16 people-oriented urbanization indicators across four dimensions, namely, economic, social, environmental, and equity dimensions, from 2005 to 2020, and their relationships with population/land urbanization at multiple scales (national, regional, and urban agglomeration scales), and among different city sizes, via the paired t test and the evenness index. Notably, between 2005 and 2020, these urbanization indicators of China showed an overall upward trend, with changes ranging from 1.09 to 53.95 times. Among the 16 people-oriented urbanization indicators, the economic and social indicators lagged behind the land and population urbanization, whereas the environmental indicators caught up. The evenness index among these indicators showed a U-shaped change pattern, which indicated that people-oriented urbanization was coming up with population/land urbanization since the implementation of China new-type urbanization plan in 2014 until 2020. In the future, increasing investment in social service systems and implementing place-based coordination strategies are necessary to make cities inclusive, safe, resilient, and sustainable.